Structural Analysis of Precast Concrete Pavements for Underground Mining Roads Using Custom 3d-Fe Software and Stochastic Approach - Brescia-Noranmbuena, L (Taylor and Francis Ltd., 2025)
The mining industry is shifting to underground operations to enhance sustainability and productivity, necessitating the construction of concrete pavements within tunnels. Traditional in-situ construction techniques are slow, adversely affecting mine productivity. As an alternative, the Accelerated Construction approach proposes the use of precast pavement slabs. However, the unique combination of precast pavements, atypical mining loads and specific support conditions cannot be analysed using traditional pavement design methods. To address the lack of a suitable design methodology, this paper presents structural analysis of precast underground mining pavements (UMP) using custom linear-elastic three-dimensional finite element method (3D-FEM) software. The study examines the impact of slab dimensions, dowel spacing and subgrade stiffness on slab stresses. Three key findings emerged: (1) Pavement stresses are highly concentrated near the tires, especially when considering the braking forces common in mining operations. (2) Random rock stiffness within the tunnel increases design stress without altering the pavements’ overall response. (3) The construction process influences slab design due to flexural stress caused by lifting forces. Overall, this paper contributes to the state-of-the-art in pavement engineering by providing a more reliable structural design methodology that incorporate an Accelerated Construction approach. © 2025 Informa UK Limited, trading as Taylor & Francis Group.